2012
DOI: 10.1080/02640414.2012.712712
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the LPM tracking system considering dynamic position changes

Abstract: This study investigates the accuracy of the tracking system LPM (local position measurement). The goal was to determine detailed error values of the system in the context of sports performance analyses. Six moderately trained male soccer players (amateur level) performed 276 runs on three different courses at six different speeds. Additionally, ten small-sided game plays were carried out. All runs and game plays were recorded with the LPM tracking system and the motion capture system VICON simultaneously. VICO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
108
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 12 publications
7
108
2
Order By: Relevance
“…Considering only the straight and 90° changeof-direction movements, the average and maximal errors of LPM average speed in our study (0.1% and 2.0%, respectively) were less than in the study of Frencken et al 15 (-2.8% and -3.9%, respectively). Furthermore, our results indicated that peak speed estimation of LPM differed between -4% and 3% (0.6% on average) from the gold standard, which is considerably less than the average relative difference of 10% found by Ogris et al 18 One of the reasons for the lower average-and peak-speed error estimation of LPM in our study compared with other studies, apart from differences in protocol, can be the newer version of the LPM system used in the current study. As already indicated by Ogris et al, 18 this newer version has improved filter algorithms, including Kalman filtering, which probably reduces position-estimation error, thereby improving the tracking of the dynamics.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…Considering only the straight and 90° changeof-direction movements, the average and maximal errors of LPM average speed in our study (0.1% and 2.0%, respectively) were less than in the study of Frencken et al 15 (-2.8% and -3.9%, respectively). Furthermore, our results indicated that peak speed estimation of LPM differed between -4% and 3% (0.6% on average) from the gold standard, which is considerably less than the average relative difference of 10% found by Ogris et al 18 One of the reasons for the lower average-and peak-speed error estimation of LPM in our study compared with other studies, apart from differences in protocol, can be the newer version of the LPM system used in the current study. As already indicated by Ogris et al, 18 this newer version has improved filter algorithms, including Kalman filtering, which probably reduces position-estimation error, thereby improving the tracking of the dynamics.…”
Section: Discussionmentioning
confidence: 40%
“…Furthermore, our results indicated that peak speed estimation of LPM differed between -4% and 3% (0.6% on average) from the gold standard, which is considerably less than the average relative difference of 10% found by Ogris et al 18 One of the reasons for the lower average-and peak-speed error estimation of LPM in our study compared with other studies, apart from differences in protocol, can be the newer version of the LPM system used in the current study. As already indicated by Ogris et al, 18 this newer version has improved filter algorithms, including Kalman filtering, which probably reduces position-estimation error, thereby improving the tracking of the dynamics. A Kalman filter is an algorithm that predicts data based on a weighting of the dynamics of previous data combined with the current measurement.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Radio-frequency tracking systems have emerged, which gather similar data to GPS, with both the Local Position Measurement (LPM) system (Frencken, Lemmink, & Delleman, 2010;Ogris et al, 2012) and the Wireless Ad-hoc System for Positioning (WASP) (Hedley et al, 2010;Sathyan, Shuttleworth, Hedley, & Davids, 2011) currently available. These systems rely on distance measurements between known fixed base stations and mobile tags worn by the athlete (Leser, Baca, & Ogris, 2011).…”
Section: Introductionmentioning
confidence: 99%